Atrial tachyarrhythmias following percutaneous device closure of secundum atrial septal defects. (April 2020) - Vyas, Vishal; Kaura, Amit; Sawhney, Vinit; Lowe, Martin; Ezzat, Vivienne
Abstract: Background: Atrial tachyarrhythmias (ATs) are a major source of morbidity in the atrial septal defect (ASD) patient cohort. The optimal timing and approach of anti-arrhythmic intervention is currently unclear. Here, we sought to determine the overall rate of ATs following percutaneous ASD closure and risk factors that may predict this. Methods: A systematic search of the literature was performed using the search terms '(Secundum Atrial Septal Defects AND Atrial arrhythmias) AND (transcatheter closure or percutaneous closure or device closure)'. All studies in English reporting the rate of ATs following percutaneous closure of secundum ASDs in adult patients were included. The primary outcome was documented AT detection during follow-up ECG monitoring. A meta-regression was then performed to test for an interaction between demographic/procedural characteristics and the primary outcome. Results: 13 observational studies including 2366 patients were analysed. The overall post-procedure AT event detection rate was 8.6%. Multivariate meta-regression analysis revealed that only male gender was associated with a higher rate of post-procedure AT detection while utilisation of the Amplatzer Septal Occluder device was associated with a lower AT detection rate and comprised 96.2% of all devices used. A high level of heterogeneity was observed (I 2 -statistic 92.3%, Q value 156.8). Conclusions: Our study illustrates that despite percutaneous ASD closure, a high proportion of adult patients have ATs with male gender correlating with higher AT rates. While the Amplatzer Septal Occluder device correlated with lower AT rates, this was the overwhelmingly the predominant device used hence comparison to other devices remains challenging.